Potential of paclobutrazol for controlling excessive growth of acacia mangium and storing recalcitrant dipterocarp seedlings for forest rehabilitation - Abod, Sheikh Ali; Fadzin, Muhamad Bokhari (Universiti Putra Malaysia Press, 2003)
Acacia mangium seedlings often overgrow in size when the timing between plant production and field planting cannot be synchronized. Dipterocarp seeds, on the other hand, are short-lived and when available need to be sown immediately for the production of planting stocks. Since conventional storage methods have not been proven to be successful in maintaining the viability of these seeds, storing their seedlings at a slow growth phase with paclobutrazol and applying gibberellic acid to induce growth recovery when needed for field planting is an attractive option. This paper reports the results of various experiments on the use of paclobutrazol and gibberellic acid for A. mangium, Shorea leprosula and S. parvifolia seedlings. The results are discussed with implications for practical application.